A bloodstream infection by Ruminococcus gnavus in a patient with a gall bladder perforation. (October 2017) - Kim, Young Jin; Kang, Hee Yoon; Han, Yujin; Lee, Mi Suk; Lee, Hee Joo
Abstract: Ruminococcus gnavus is frequently found among human gut microbiome. However, human bloodstream infections by R. gnavus have been reported only three times. Clinical details were lacking for one case; the other two cases with concurrent bacteremia in patients with diverticulitis. We report a case of R. gnavus bloodstream infection in a patient with a gall bladder perforation suggesting its association with damage to the gastrointestinal tract. R. gnavus was misidentified using biochemical test but 16S rRNA sequencing and Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry were useful for correct identification. With the advancement of identification method in clinical laboratory, more frequent identification of R. gnavus from clinical specimens is expected. Highlights: We report a bacteremia caused by Ruminococcus gnavus in a patient with a gall bladder perforation. This bacteria is human gut flora and could be misidentified by conventional biochemical methods. R. gnavus was identified correctly through 16S rRNA sequencing and MALDI-TOF MS. More clinical isolates are expected to be found owing to development of identification methods.